LABORATORY RESULTS THAT SUGGEST USING PROGNOSTIC MARKERS IN ASSESSMENT AND DIAGNOSIS OF RHEUMATOID ARTHRITIS - Spasovski, Dejan; Sandevska, Emilija; Veljanovska, Aleksandra Pivkova; Balkanov, Svetlana Krstevska (Journal of Morphological Sciences, 2022)
ESR and CRP reactants reflect synovitis indirectly. Simultaneously, they are the cause of objectivization and measurement of immune-mediated inflammatory responses in RA. CRP, RF, and ESR testing accompanied with clinical variables of inflammatory synovitis are suggested to evaluate the disease’s activity. Aim: Assessment of RA’s activity with the reactants of the acute phase, ESR, CRP, and RF as prognostic markers for disease activity in patients treated with Methotrexate for early RA. This study focuses on 70 patients in total: 35 patients with early RA and 35 patients in the healthy control group. Patients (pts) were given Methotrexate once a week at a dose of 10 mg on average. We were able to analyze ESR, RF, and CRP in every patient at certain time intervals (0 times, after 6, 9, and 12 months). RA was assessed following the dynamics of changes in the mean values of CRP, RF, and ESR. The analysis showed statistically notable differences among the mean values of ESR in the four-time intervals (p=0,00002). The mean values of CRP also showed differences in all four-time intervals (p=0,0428). On the other hand, no noteworthy statistical differences were detected among the mean values of RF in the four-time intervals (p=0,573). High values of CRP and RF were detected in most patients. The process of disease progression continues despite the Methotrexate therapy, especially in those patients that have elevated values of ESR, CRP, and RF. They are shown to be predictors of the aggressive course of the disease. This enables the selection of the high-risk group of patients for an aggressive course of the disease and points to the necessity for early and aggressive treatment. Keywords : RA (Rheumatoid Arthritis); RF (Rheumatoid Factor); reactants of the acute phase; CRP. https://doi.org/10.55302/JMS2251157s